2015
DOI: 10.1016/j.biomaterials.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Lhx8 mediated Wnt and TGFβ pathways in tooth development and regeneration

Abstract: LIM homeobox 8 (Lhx8) is a highly conserved transcriptional factor with recently illustrated roles in cholinergic and GABAergic differentiation, and is expressed in neural crest derived craniofacial tissues during development. However, Lhx8 functions and signaling pathways are largely elusive. Here we showed that Lhx8 regulates dental mesenchyme differentiation and function via Wnt and TGFβ pathways. Lhx8 expression was restricted to dental mesenchyme from E11.5 to a peak at E14.5, and absent in dental epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…14,15 Numerous studies have confirmed that signalling pathways, growth factors and epigenetic regulators are involved in the odontoblastic differentiation process of hDPCs. [16][17][18] Our previous studies indicated for the first time that all TETs were expressed in the nucleus and cytoplasm of hDPCs, and only TET1 expression was elevated during both early spontaneous differentiation and odontoblastic induction. 19 Moreover, TET1 knockdown suppresses the odontoblastic differentiation potential of hDPCs.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…14,15 Numerous studies have confirmed that signalling pathways, growth factors and epigenetic regulators are involved in the odontoblastic differentiation process of hDPCs. [16][17][18] Our previous studies indicated for the first time that all TETs were expressed in the nucleus and cytoplasm of hDPCs, and only TET1 expression was elevated during both early spontaneous differentiation and odontoblastic induction. 19 Moreover, TET1 knockdown suppresses the odontoblastic differentiation potential of hDPCs.…”
Section: Introductionmentioning
confidence: 86%
“…Human dental pulp cells (hDPCs) are of mesenchymal origin and exhibit high proliferative and self‐renewal capacity, and they possess the ability to differentiate into odontoblast‐like cells, which are required for reparative dentinogenesis when caries or trauma occurs . Numerous studies have confirmed that signalling pathways, growth factors and epigenetic regulators are involved in the odontoblastic differentiation process of hDPCs . Our previous studies indicated for the first time that all TETs were expressed in the nucleus and cytoplasm of hDPCs, and only TET1 expression was elevated during both early spontaneous differentiation and odontoblastic induction .…”
Section: Introductionmentioning
confidence: 99%
“…This expression continues to be restricted to the dental papilla and the odontoblast, and gradually decreases over time [22]. The differentiation and function of the dental mesenchyme are regulated by Lhx8 via WNT and TGFβ pathways [23]. FGF9 is also involved in epithelial invagination and initiation of ectodermal organogenesis [24].…”
Section: Fgfsmentioning
confidence: 99%
“…During these processes, a number of growth factors, such as transforming growth factor‐β (TGF‐β), fibroblast growth factor, platelet‐derived growth factors, etc., may be released from the dentin matrix and regulate the pulp cells and mesenchymal cells, and thus induce reactionary and reparative dentinogenesis (Smith et al , ; Tziafas et al , ). TGF‐β alone or in combination with other scaffolds, such as collagen, porous chitosan membrane, calcium phosphate cement, etc., have been successfully used for tissue engineering, dentinogenesis and regeneration of pulpo‐dentin complex in vivo (Hu et al , ; Li et al , ; Tziafas et al , ; Zhang et al ., ; Zhou et al , ).…”
Section: Introductionmentioning
confidence: 98%